Intra-abdominal Trocar-Free Vacuum Liver Retractor for Upper-Gastrointestinal Surgery: Preliminary Clinical Series Using the LiVac System. (April 2017) - Benzing, Christian; Weiss, Helmut; Krenzien, Felix; Biebl, Matthias; Pratschke, Johann; Zorron, Ricardo
Background . In laparoscopic upper-gastrointestinal (GI) surgery, an adequate retraction of the liver is crucial. Especially in single-port surgery and obese patients, problems may occur during liver retraction. The current study seeks to evaluate the efficacy and safety of the LiVac trocar-free liver retractor in laparoscopic upper-GI surgery. Methods . The present study is a nonrandomized dual-center clinical series describing our preliminary results using the LiVac system for liver retraction. The primary end points of the present study included the effectiveness and safety of the LiVac device as well as complications and documentation of problems with the device during surgery. Results . The device was used in 11 patients for simple and complex laparoscopic procedures. The mean age of the study population was 59.6 years (SD = 20.6; range = 30-84). There were 6 female and 5 male patients with a mean body mass index (BMI) of 31.9 kg/m 2 (SD = 8.1; range = 26.0-45.3). The efficacy of the device was excellent in all cases, reducing the number of trocars needed. There were no device-related complications. Conclusion . The LiVac liver retractor is easy to use and provides a good exposure of the operative field in upper-GI laparoscopic surgery, even in obese patients with a high BMI.